BENTUK PROGRAM CORPORATE SOCIAL RESPONSIBILITY BANK NAGARI CABANG PANGKALAN DAN MANFAATNYA BAGI KEHIDUPAN SOSIAL EKONOMI MASYARAKAT LOKAL - Nela Hari Zona (Perspektif Sosiologi, 2013)
The purpose of this study was to determine the form of Bank Nagari CSR programs and socio-economic benefits for local communities. The research method used was a qualitative research method. The results showed that the CSR program in the form of Bank Nagari Branch Pangkalan philanthropy (philanthropy). The program embodied in various forms of philanthropic activities by the Bank Nagari as a form of concern for the local community. The program is in the field of education, religion, culture, arts and sports, and social. Bank Nagari CSR program can provide socio-economic benefits to local communities during the program organized by the Bank Nagari. However, CSR programs Bank Nagari Branch Pangkalan does not provide long-term benefit for the social and economic life of local communities. Bank Nagari in general and Bank Nagari Branch Pangkalan in particular, are expected to be able to carry out CSR programs based on community empowerment so that the impact of the program can be felt by the community in the long run. Keywords : Corporate Social Responsibility, business, and local community.